A Philanthropic Approach to Combating Homelessness: The Role of the Mosques in İstanbul - Mustafa Fazıl Karaman (İstanbul Üniversitesi Sosyoloji Dergisi)
This study explores how mosques, as pillars of the philanthropic tradition, can address homelessness. It initially outlines homelessness and the deeply rooted philanthropic tradition in Turkish-Islamic culture. Subsequently, the research findings are presented. Understanding mosques’ services to homeless individuals as visible symbols of philanthropy and social life regulators within Turkish-Islamic culture is crucial. Interviews with the imams of four prominent Istanbul mosques analysed their activities for the homeless. Findings were categorised into six themes: “reasons for homelessness studies,” “causes of homelessness,” “mosques’ protection against dangers,” “mosques’ role in social inclusion,” “mosques’ role in solving homelessness,” and “the importance of the Directorate of Religious Affairs.” This study examines the social and psychological aspects of mosques’ activities for homelessness and their potential. Findings highlight the significance of activating the philanthropic tradition, especially in mosques, to combat homelessness among marginalised groups. Mosques, with their social-psychological functions, offer substantial opportunities to support homelessness initiatives.